Isatin thiazoles as antidiabetic: Synthesis, in vitro enzyme inhibitory activities, kinetics, and in silico studies. Issue 6 (30th March 2022) - Solangi, Mehwish; Kanwal,; Khan, Khalid M.; Chigurupati, Sridevi; Saleem, Faiza; Qureshi, Urooj; Ul‐Haq, Zaheer; Jabeen, Almas; Felemban, Shatha G.; Zafar, Fatima; Perveen, Shahnaz; Taha, Muhammad; et al.
Abstract: Diabetes mellitus is one of the most prevalent diseases nowadays. Several marketed drugs are available for the cure and treatment of diabetes, but there is still a dire need of introducing compatible drug molecules with lesser side effects. The current study is based on the synthesis of isatin thiazole derivatives 4–30 via the Hantzsch reaction. The synthetic compounds were characterized using different spectroscopic techniques and evaluated for their α‐amylase and α‐glucosidase inhibition potential. Of 27 isatin thiazoles, five (4, 5, 10, 12, and 16 ) displayed good activities against the α‐amylase enzyme with IC50 values in the range of 22.22 ± 0.02–27.01 ± 0.06 µM, and for α‐glucosidase, the IC50 values of these compounds were in the range of 20.76 ± 0.17–27.76 ± 0.17 µM, respectively. The binding interactions of the active molecules within the active site of enzymes were studied with the help of molecular docking studies. In addition, kinetic studies were carried out to examine the mechanism of action of the synthetic molecules as well. Compounds 3a, 4, 5, 10, 12, and 16 were also examined for their cytotoxic effect and were found to be noncytotoxic. Thus, several molecules were identified as good antihyperglycemic agents, which can be further modified to enhance inhibition ability and to find the lead molecule that can act as a potential antidiabetic agent. Abstract : Isatin thiazole derivatives 4–30 were synthesized via the Hantzsch reaction and evaluated for their α‐amylase and α‐glucosidase inhibition potential. Compounds 4, 5, 10, 12, and 16 displaying good activities against α‐amylase and α‐glucosidase were further studied for their binding interactions in the active site of the enzymes. Kinetic studies were carried out to examine the mechanism of action of the synthetic molecules.